1988
DOI: 10.2307/1941249
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Annuals in Competitive Neighborhoods: Effects of Elevated CO2

Abstract: Four members of an annual community were used to investigate the effects of changing neighborhood complexity and increased CO2 concentration on competitive outcome. Plants were grown in monoculture and in all possible combinations of two, three, and four species in CO2—controlled growth chambers at CO2 concentrations of 350, 500, and 700 μL/L with ample moisture and high light. Species responded differently to enhanced CO2 level. Some species (e.g., Abutilon theophrasti) had increased biomass with increasing C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 7 publications
1
53
0
Order By: Relevance
“…Since photosynthesis of C3 plant species is not saturated at the present ambient CO 2 concentration, these plants are thus reported to benefit more than C4 plants (Bowes 1993;Joshi 2006). Average increase of about 33 % in the rate of photosynthesis and productivity of C3 plants has been reported with doubling of atmospheric CO 2 concentration (Kimball 1983;Bazzaz and Garbutt 1988;Cure andAcock 1986, Joshi 2006). In the present investigation, under elevated CO 2 concentration (700 μmol mol −1 ) the photosynthetic rate of Cannabis sativa was~44 % higher relative to that under ambient CO 2 (390 μmol mol −1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since photosynthesis of C3 plant species is not saturated at the present ambient CO 2 concentration, these plants are thus reported to benefit more than C4 plants (Bowes 1993;Joshi 2006). Average increase of about 33 % in the rate of photosynthesis and productivity of C3 plants has been reported with doubling of atmospheric CO 2 concentration (Kimball 1983;Bazzaz and Garbutt 1988;Cure andAcock 1986, Joshi 2006). In the present investigation, under elevated CO 2 concentration (700 μmol mol −1 ) the photosynthetic rate of Cannabis sativa was~44 % higher relative to that under ambient CO 2 (390 μmol mol −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Doubling in CO 2 concentration has been reported to increase the yield by 30 % or more in many crops (Poorter 1993). On the other hand, inhibition of photosynthesis with increasing CO 2 concentration has also been reported in many plant species (Bazzaz and Garbutt 1988;Juurola 2003). Cannabis sativa L. (Cannabaceae) is a widely distributed plant around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Strain & Cure 1985), and that it can significantly alter competitive relationships and outcomes among genotypes within populations (Curtis et al 1996;Schmid, Birrer & Lavigne 1996;Tousignant & Potvin 1996) and among species in communities (e.g. Bazzaz & Carlson 1984;Zangerl & Bazzaz 1984;Williams et al 1986;Bazzaz & Garbutt 1988;Bazzaz et al 1989;Arp et al 1993;Johnson, Polley & Mayeux 1993;Owensby et al 1993;Arnone & Körner 1995;Arnone 1996;Chiariello & Field 1996;Leadley & Körner 1996), it is unclear to what extent these changes can be attributed to altered competitive relationships among root systems. This is particularly the case for interactions among crops and their associated weed species where reductions in crop yield as a result of weed competition (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Bazzaz and Garbutt, 1988;Schlesinger et al, 2006]. An increase of 30% in modern atmospheric CO 2 over preindustrial levels due to human activities has been shown [e.g.…”
Section: Discussionmentioning
confidence: 99%